Malted Multi-millet based Probiotic Dairy Beverage: Nutritional, Sensory, Physicochemical and Microbiological Characterization - G. Swarnalatha; S. Sharath Kumar; T. V. Madhavi (International Journal of Economic Plants, 2025)
In the current study conducted during November, 2023–April, 2024 , malted multimillet flours (MMF) viz., Finger millet, Foxtail millet and Little millet were used for preparation of probiotic lassi. The millet grains were soaked in water, the steeped grains were incubated at 25ºC 24 h-1 for germination and  dried in a vacuum tray dryer maintained at 40°C 6 h-1. The dried millet grains were ground into fine powder using commercial flour mill. The equal amount of malted mixed millet flour was used for product preparation.The MMF was incorporated in standardized milk at the rate of 5, 10, 15, 20 and 25% and fermented using probiotic culture containing Lactobacillus acidophilus, Bifidobacterium and Streptococcus thermophilus. Control lassi was prepared without addition of multimillet flour. Samples were analysed for proximate composition, sensory, titratable acidity, pH and microbiological parameters. The sensory attributes was measured by using 9 point hedonic scale by panel of semi trained judges. The results revealed that increase in incorporation of multi millet flour had a significant affect (p<0.05) on quality attributes. MMF incorporated products showed higher titratable acidity. The acidity and probiotic count were increased with increased rate of millet incorporation. The probiotic beverage showed above 108 CFU ml-1 count and improved nutritional and physicochemical profiles, compared to control. Even though the sensory attributes of 15% incorporated MMF probiotic lassi was significantly found superior to control and other concentrations.